The Family Psychoeducation to Improve Parents' Coping Strategies in Caring for Thalassemia Children - Mariani, Dini; Muffidah, Annisa Salwa; Rosdiana, Ida (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Thalassemia is a genetic disorder of the synthesis of alpha or beta globin chains, either in whole or in part. Families who care for children with thalassemia will experience psychosocial problems. Ignorance is the reason why families find it difficult to adapt. Therefore, it is necessary to provide knowledge and the ability to adapt to stressors so that family coping is positive. This study aims to determine the effect of Family Psychoeducation on parents' coping strategies in caring for children with thalassemia. The research design used a "Quasi experiment pre-post-test with a control group." The purposive sampling technique was used with a sample of 44 people divided into two groups. The instrument used is Brief COPE. The results showed that in the intervention group, there was a significant difference in the average score with a p-value of 0.000. Meanwhile, in the control group, there was no significant difference in the average score with a p-value of 0.492. There is a difference in the average score between the intervention group and the control group, with a p-value of 0.023. In conclusion, there is an influence of family psychoeducation on parents' coping strategies in caring for children with thalassemia.